The codon sequences predict protein lifetimes and other parameters of the protein life cycle in the mouse brain. Issue 1 (December 2018) - Mandad, Sunit; Rahman, Raza-Ur; Centeno, Tonatiuh; Vidal, Ramon; Wildhagen, Hanna; Rammner, Burkhard; Keihani, Sarva; Opazo, Felipe; Urban, Inga; Ischebeck, Till; Kirli, Koray; Benito, Eva; et al.
Abstract The homeostasis of the proteome depends on the tight regulation of the mRNA and protein abundances, of the translation rates, and of the protein lifetimes. Results from several studies on prokaryotes or eukaryotic cell cultures have suggested that protein homeostasis is connected to, and perhaps regulated by, the protein and the codon sequences. However, this has been little investigated for mammalsin vivo . Moreover, the link between the coding sequences and one critical parameter, the protein lifetime, has remained largely unexplored, bothin vivo andin vitro . We tested this in the mouse brain, and found that the percentages of amino acids and codons in the sequences could predict all of the homeostasis parameters with a precision approaching experimental measurements. A key predictive element was the wobble nucleotide. G-/C-ending codons correlated with higher protein lifetimes, protein abundances, mRNA abundances and translation rates than A-/U-ending codons. Modifying the proportions of G-/C-ending codons could tune these parameters in cell cultures, in a proof-of-principle experiment. We suggest that the coding sequences are strongly linked to protein homeostasisin vivo, albeit it still remains to be determined whether this relation is causal in nature.